1995
DOI: 10.1007/bf02445003
|View full text |Cite
|
Sign up to set email alerts
|

Criteria of individual and population-wide resistance to acute hypoxia

Abstract: It is shown that the geometric mean of survival time and the deviation of ~ from x are measures of a population's resistance to acute hypoxia; that a measure of the individual resistance of an animal to such hypoxia is Student's parameter for that animal; that the distribution of Student's parameter in a population is a lognormal distribution under any conditions; and that the number of animals with low resistance is always equal to the number of highly resistant animals. The procedure described makes it possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Because of asymmetry, the center of distribution was most precisely characterized by the median [5]. The mean suggested tbr this purpose in [4] was higher than the median, while the geometric mean proposed in [1 ] was lower. The variations in the group size during the day (HR group was always the smallest) was probably due to the difference between theoretical and empirical distributions.…”
Section: Eelmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of asymmetry, the center of distribution was most precisely characterized by the median [5]. The mean suggested tbr this purpose in [4] was higher than the median, while the geometric mean proposed in [1 ] was lower. The variations in the group size during the day (HR group was always the smallest) was probably due to the difference between theoretical and empirical distributions.…”
Section: Eelmentioning
confidence: 99%
“…These variations is probably due to differences between empirical and theoretical samples, which is evidenced by its highest value at the beginning of the day when the sample sizes were not as large as later on. Thus, dally variations of SP values in Wistar rats, like dally and seasonal variations in outbred rats [l ], were described by a log-normal distribution [1]. The log-normal distribution was typical not only of large (n=104-139), but also of relatively small (n=11-63) samples.…”
Section: Eelmentioning
confidence: 99%
See 2 more Smart Citations
“…Special normobaric and hypobaric tests make it possible to classify the animals as high-(HR), medium-(MR) and low-resistant (LR) to hypoxia [1][2][3]6,9]. Biochemical studies showed that animals with different resistance to hypoxia differ not only in parameters of energy, lipid, and carbohydrate metabolism [2,6], but also in the functional characteristics of hemodynamic regulation.…”
Section: Abstract: Acute Hypoxia; Hemodynamics; Respiration; Individmentioning
confidence: 99%